Case analysis of occupational disease diagnosis appraisal in Shanghai from 2012 to 2024 - Ran ZHUANG; Tingting DOU; Jing QU; Tongning GAO; Lili PU; Yan YIN (环境与职业医学)
BackgroundOccupational disease diagnosis appraisal is an appeal procedure initiated when a party disagrees with the occupational disease diagnosis conclusion. It is a legal procedure to safeguard the health rights of employees and the legitimate rights and interests of employers.ObjectiveTo analyze the data of occupational disease diagnosis appraisal in Shanghai, identify existing problems, and provide suggestions for improving. MethodsStatistical analysis was conducted on basic situation, characteristics of workers and employers, disease classification, and consistency between diagnosis and appraisal conclusions of all occupational disease diagnosis appraisal cases from 2012 to 2024. All diagnosis conclusions were named in accordance with the Classified Catalogue of Occupational Diseases included employers were classified according to the Measures for the Statistical Classification of Large, Medium, Small and Micro Enterprises" and the Notice on Adjusting the Provisions for Classifying Enterprise Registration Types; industry classification followed the Industrial Classification for National Economic Activities (GB/T 4754-2017).ResultsFrom 2012 to 2024, a total of 260 cases of occupational diseases diagnosis appraisal were closed. The main diagnosis were 138 cases of ear, nose, throat, and oral diseases (53.1%), chemical poisoning (18.8%), and pneumoconiosis and other respiratory diseases (16.2%). The proportion of ear, nose, throat, and oral diseases gradually increased (2022 excluded). The incidence of annual municipal and provincial cases decreased by 76.3% and 85.0% respectively (2024 vs 2012). The consistency rate of conclusions between appraisal and diagnosis gradually increased. The total consistency rates between final appraisals and diagnostic conclusions were 81.5%, and 79.7%, 87.8%, 100.0%, 85.0% for ear, nose, throat, and oral diseases, chemical poisoning, and pneumoconiosis and other respiratory system diseases, respectively. Specifically, the consistency rates were 80.1% and 80.0% for noise-induced deafness and chronic benzene poisoning. In terms of inconsistency reasons, "inconsistent interpretation of standards and excessive discretion in standard application" accounted for 43.8%, followed by "failure to correctly apply standards" (31.3%) and and "discrepancies in occupational exposure history recognition" (15.6%).ConclusionThe revisions and improvements of the legal system for occupational disease diagnosis appraisal have played a positive role in improving the consistency of conclusions between appraisal and diagnosis of occupational diseases in Shanghai. It is suggested to further strengthening the publicity and training of occupational disease diagnosis standards to improve the quality of occupational disease diagnosis.